2019
DOI: 10.1038/s41467-018-08070-4
|View full text |Cite
|
Sign up to set email alerts
|

Half a degree and rapid socioeconomic development matter for heatwave risk

Abstract: While every society can be exposed to heatwaves, some people suffer far less harm and recover more quickly than others from their occurrence. Here we project indicators of global heatwave risk associated with global warming of 1.5 and 2 °C, specified by the Paris agreement, for two future pathways of societal development representing low and high vulnerability conditions. Results suggest that at the 1.5 °C warming level, heatwave exposure in 2075 estimated for the population living in low development countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 33 publications
1
64
0
Order By: Relevance
“…King and Harrington (2018) indicated that the ratios of annual mean temperature differences (2.0°C minus 1.5°C) and the internal variability are larger in lower-income countries. Russo et al (2019) suggested that heatwave exposure and an illustrative heatwave risk index (the product of the probability of heatwave occurrence, exposure and a proxy for vulnerability) at the 1.5°C warming level for the population living in low development countries is expected to be greater than those at the 2°C warming level for the population living in very high development countries. Döll et al (2018) showed that the effect on ΔQ 7hf of meeting the 1.5°C goal rather than the 2.0°C would be felt more strongly in the low-income country groups than other country groups.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…King and Harrington (2018) indicated that the ratios of annual mean temperature differences (2.0°C minus 1.5°C) and the internal variability are larger in lower-income countries. Russo et al (2019) suggested that heatwave exposure and an illustrative heatwave risk index (the product of the probability of heatwave occurrence, exposure and a proxy for vulnerability) at the 1.5°C warming level for the population living in low development countries is expected to be greater than those at the 2°C warming level for the population living in very high development countries. Döll et al (2018) showed that the effect on ΔQ 7hf of meeting the 1.5°C goal rather than the 2.0°C would be felt more strongly in the low-income country groups than other country groups.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Some studies have suggested that the frequencies of hot days will increase more rapidly in the poorest countries in the tropics than in countries in mid-tohigh-latitude regions (Mahlstein et al 2011, Harrington et al 2016, Hoegh-Guldberg et al 2018. It has been suggested that 1.5°C-2°C differences of increases in heatwave exposure (Russo et al 2019), high streamflow (Döll et al 2018) and multi-sector (water, energy, food and environment) risks (Byers et al 2018) are larger for low-income countries/populations than high-income countries/populations.…”
Section: Introductionmentioning
confidence: 99%
“…Reliable forecasting of air temperature at 2 m above the land surface plays a significant role when preparing for potential weather‐related disasters, such as heat waves (i.e., maximum daytime air temperature) and cold spells (i.e., minimum nighttime air temperature). Extreme air temperatures can also cause various social and economic problems such as heat‐related disease and high energy consumption (Klinenberg, 2015; Russo et al, 2019). In particular, the increasing intensity, frequency and duration of extreme air temperatures during the summer season (Perkins et al, 2012), and the fact that more than half of the Earth's population now lives in cities (Schulze & Langenberg, 2014) suggest that accurate air temperature forecasting is essential for urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…The most direct impacts of climate change are increases in the frequency and intensity of extreme weather events (or natural disasters), such as heatwaves, droughts, wildfire, storms, and sea‐level rise (Field, Barros, Stocker, & Dahe, ). Projected frequency of extreme heat waves at 1.5 or 2°C of warming is drastically higher for Africa, Latin America, Middle East, and some Southeast Asian countries than for other parts of the world (Russo et al., ). In particular, heatwaves in Africa have accelerated in the last few decades and are projected to occur regularly by 2040 if the current trend of emissions continues (Russo, Marchese, Sillmann, & Immé, ).…”
Section: Climate Change Impacts and Adaptation In Developing Countriesmentioning
confidence: 99%